ปัจจัยทางการตลาดที่มีผลต่อการขนส่งสินค้าเกษตรด้วยระบบตู้คอนเทนเนอร์ทางรถไฟ - เจริญ วาริพันธน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
This thesis aims at studying inland container transport by train of agricultural products of the manufacturers and exporters in the North East of Thailand. It also focuses on the marketing factors (the 8Ps) influencing inland container transport by train of agricultural products for export by the manufacturers in the North East. Furthermore, it aims at studying measures to improve and develop inland container transport by train of the agricultural products of the nationwide sampling tapioca manufacturers and exporters. The studies conclude that 38% of the sampling group did not get any information regarding inland container transport, while 62 % were aware but did not know about the charges for transportation by train. All of the sampling group hired the transportation companies to transport their products due to conveniences. They do not favor train transportation because of unsuitable train routes, double handling and slow services. The studies reveal the most important factor influencing inland container transport by train was the factor regarding the process of the service. From the study of different level of importance of the marketing factors combination by influencing the marketing service (the 8 Ps), which led the manufacturers to use inland container transport by train, it was found that at 0.05 significant difference for manufacturers from different locations, it was not statistically significant. From the studies, it is recommended that the State Railway of Thailand need to improve their service to customers and to transportation companies (3[superscript rd] Party). They should improve the service by considering level of the marketing factors importance. The strategy is to improve service standard to meet the needs of different regional customers. They should also increase the capacities of transportation by train to Lam Chabang Port to meet the increasing demand of delivery in the future.